Contemporary Dimensions of Social Commerce - Danchev, Dancho (Research Papers, 2023)
The current global aspects of social commerce, as a business model combining online commerce and social networks, are under consideration. Emphasis is placed on the conceptualization of this commercial and social phenomenon, indicating the main characteristics and elements of social commerce. The advantages and benefits of social commerce for retailers and consumers are emphasized, its successful development is tracked and the factors that determine modern trends are analysed. Some guidelines for increasing sales in social commerce (STP, omnichannel strategies, personalization, quality content, communication, advertising, etc.) are outlined, as well as the challenges in its development (personal data protection, difficulties for small businesses, adequate inventory, encourage the use of social media to make purchases).